Making Simple Repairs: Holes in the Wall - Mary N. Harrison (EDIS)
Landlords will deduct money from your security deposit if they have to fill in holes when you leave. You can save money by filling small holes yourself. This document is FCS5234-02, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.